The transition between walking and running in humans: metabolic and mechanical aspects at different gradients - Minetti, A. E.; Ardigo, L. P.; Saibene, F. (Acta Physiologica Scandinavica, 1994)
Five subjects walked and ran at overlapping speeds and different gradients on a motorized treadmill. At each gradient the speed was obtained at which walking and running have the same metabolic cost (Sm) and the speed of spontaneous (Ss) transition between the two gaits was measured. Ss was found to be statistically lower than Sm at all gradients, the difference being in the range of 0.5-0.9 km h-1. The motion analysis of walking reveals that at all gradients and at increasing speed: (1) the percentage of recovery, an index of mechanical energy saving related to the pendulum-like characteristic of walking, decreases; (2) the lower limb spread reaches a limit in walking; and consequently (3) both the stride frequency and the internal mechanical work, due to limb acceleration in relation to the body centre of mass, increase much more in walking than in running. Switching to a run, although implying a higher frequency, makes the internal work decrease as a result of the lower limb spread. In this paper several influences, such as the `ratings of perceived exertion` (RPE), on the choice of beginning to run when it is more economical to walk, are discussed. A tentative hypothesis on the determinants of Ss, which is emphasized to be a speed which has to be studied in detail but is generally avoided in locomotion, is based on a comfort criterion from peripheric afferences and is reflected by the fact that at Ss a running stride costs as much as a walking stride. A preliminary measure of the subjects' behaviour during spontaneous overground locomotion, where the progression speed can be changed freely, reveals that the running speed immediately following gait transition is approximately 2 km h-1 higher than the `last` walking speed, supporting the hypothesis of metabolic energy minimization.